The lateral superior olive in the mouse: Two systems of projecting neurons - Williams, Isabella R.; Filimontseva, Anastasia; Connelly, Catherine J.; Ryugo, David K. (Frontiers in Neural Circuits, 2022)
The lateral superior olive (LSO) is a key structure in the central auditory system of mammals that exerts efferent control on cochlear sensitivity and is involved in the processing of binaural level differences for sound localization. Understanding how the LSO contributes to these processes requires knowledge about the resident cells and their connections with other auditory structures. We used standard histological stains and retrograde tracer injections into the inferior colliculus (IC) and cochlea in order to characterize two basic groups of neurons: (1) Principal and periolivary (PO) neurons have projections to the IC as part of the ascending auditory pathway; and (2) lateral olivocochlear (LOC) intrinsic and shell efferents have descending projections to the cochlea. Principal and intrinsic neurons are intermixed within the LSO, exhibit fusiform somata, and have disk-shaped dendritic arborizations. The principal neurons have bilateral, symmetric, and tonotopic projections to the IC. The intrinsic efferents have strictly ipsilateral projections, known to be tonotopic from previous publications. PO and shell neurons represent much smaller populations (<10% of principal and intrinsic neurons, respectively), have multipolar somata, reside outside the LSO, and have non-topographic, bilateral projections. PO and shell neurons appear to have widespread projections to their targets that imply a more diffuse modulatory function. The somata and dendrites of principal and intrinsic neurons form a laminar matrix within the LSO and share quantifiably similar alignment to the tonotopic axis. Their restricted projections emphasize the importance of frequency in binaural processing and efferent control for auditory perception. This study addressed and expanded on previous findings of cell types, circuit laterality, and projection tonotopy in the LSO of the mouse.